Clinical and radiological evaluation of a template‐guided (NobelGuide™) treatment concept. Issue 1 (18th September 2012) - Vasak, Christoph; Kohal, Ralf J.; Lettner, Stefan; Rohner, Dennis; Zechner, Werner
Abstract Objectives The study was designed to evaluate the clinical use of the NobelGuide™ concept over a follow‐up period of 12 months with respect to implant success and survival rates, development of soft tissue condition and recording of potential surgical and prosthetic complications. In addition, radiological assessment of peri‐implant bone levels was performed at the 1‐year follow‐up post‐implant placement. Material and methods Thirty patients (male/female = 15/15) with partially dentate and edentulous mandibles and maxillae were included. All patients were planned and operated on using the computer‐aided, template‐guided treatment concept NobelGuide™. Overall, 163 implants (NobelReplace® Tapered Groovy) were placed (mandible/maxilla = 107/56 implants). Recall appointments were performed after 1–2 weeks, 1, 3, 6 and 12 months after implant placement. Clinical parameters of the soft tissue conditions [e.g. bleeding on probing (BoP), pocket probing depth ≥3 mm (PPD), marginal plaque index (mPI)] and the dentist's esthetic and functional evaluation using a visual analogue scale (VAS) were documented. Marginal bone level was evaluated on radiographs made at implant insertion and at the 1‐year follow‐up. Results All 30 patients with 161 implants completed the 1‐year follow‐up resulting in a cumulative survival rate of 98.8% (two implant losses). Clinical parameters improved in a majority of the implants. The mean marginal bone level at implant insertion and at 1‐year follow‐up was reported with 0.17 mm (SD 1.24; n = 125) and −1.39 mm (SD 1.27; n = 110), respectively. The mean change in bone level from implant insertion to 1 year was −1.44 mm (SD 1.35; n = 98). Conclusions The 1‐year follow‐up showed a cumulative survival rate and success rate of 98.8% and 96.3%, respectively. Immediate or delayed loading of implants using a flapless, guided surgery approach (NobelGuide™) appears to be a viable concept demonstrating good clinical and radiographic outcomes at the 1‐year time point.